Applications of Evolutionary Computing EvoWorkshops 2009: EvoCOMNET, EvoENVIRONMENT, EvoFIN, EvoGAMES, EvoHOT, EvoIASP, EvoINTERACTION, EvoMUSART, EvoNUM, EvoSTOC, EvoTRANSLOG,Tübingen, Germany, April 15-17, 2009, Proceedings - Giacobini, Mario; Brabazon, Anthony; Cagnoni, Stefano; Ekart, Aniko; Esparcia-Alcázar, Anna I.; Farooq, Muddassar; Fink, Andreas; Machado, Penousal; McCormack, Jon; O'Neill, Michael; Neri, Ferrante; Preuss, Mike; et al. (Theoretical Computer Science and General Issues, 2009)
This book constitutes the refereed joint proceedings of eleven European workshops on the Theory and Applications of Evolutionary Computation, EvoWorkshops 2009, held in Tübingen, Germany, in April 2009 within the scope of the EvoStar 2009 event. The 68 revised full papers and 23 revised short papers presented were carefully reviewed and selected from a total of 143 submissions. With respect to the eleven workshops covered, the papers are organized in topical sections on telecommunication networks and other parallel and distributed systems, environmental issues, finance and economics, games, design automation, image analysis and signal processing, interactive evolution and humanized computational intelligence, music, sound, art and design, continuous parameter optimisation, stochastic and dynamic environments, as well as transportation and logistics.